SELEKCIJA MLADIH ZA SPRINT - Milan Šolaja (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
For the success in work on the speed of running (sprint), it is necessery to make an optimal screening of talented children (since the sprint speed is highly gentically predisposed). In order to make the selection relevant, it is essential to apply whole series of tests the choice of which is done based on the motor structure of sprint. Optimal design of the tests and their results in the intail measurement are not representative enought to be used to make relevant conclusions. Thet is why it is necessary to do retests after a certain period of time (12 to 18 months) to rule out accelerators in growth and development and single out really talented children who have the high abilty of progress in sprint. Based on the attached table we can see which of the children are above or below their age average, which can be helpful in the selection of talents